Solve for t 28+6t=7(t+4)

Math
28+6t=7(t+4)
Simplify 7(t+4).
Tap for more steps…
Apply the distributive property.
28+6t=7t+7⋅4
Multiply 7 by 4.
28+6t=7t+28
28+6t=7t+28
Move all terms containing t to the left side of the equation.
Tap for more steps…
Subtract 7t from both sides of the equation.
28+6t-7t=28
Subtract 7t from 6t.
28-t=28
28-t=28
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Subtract 28 from both sides of the equation.
-t=28-28
Subtract 28 from 28.
-t=0
-t=0
Multiply each term in -t=0 by -1
Tap for more steps…
Multiply each term in -t=0 by -1.
(-t)⋅-1=0⋅-1
Multiply (-t)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1t=0⋅-1
Multiply t by 1.
t=0⋅-1
t=0⋅-1
Multiply 0 by -1.
t=0
t=0
Solve for t 28+6t=7(t+4)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top